QUALITY AUDIT MEDIATION ON TENURE AUDIT AND FIRM SIZE OF DELAY AUDIT IN ISLAMIC COMMERCIAL BANKS - Africano, Fernando; Dewantara, Billy; Nugraha, Yoga Aji; Burhan, Abi (Journal Of Islamic Ekonomic and Business, 2023)
This study aims to determine the effect on tenure audit and Firm Size of delay audit mediated by quality audit in Islamic commercial banks for 2015-2019. The population includes up to 14 Islamic Commercial Banks and spans the years 2015–2019. 13 banks were included in the research sample, which was selected using a purposive sampling technique and a few criteria. Path Analysis using IBM SPSS is used for data analysis in research. The results of this study indicate that tenure audit and firm size have no direct effect on delay audit. Meanwhile, quality audit directly affects delayed audit. Tenure audit and Firm Size affect the quality of audit. Quality audit in this study can mediate full mediation of the relationship between tenure audit with delayed audit, and Firm Size with delayed audit.